Penentuan Jumlah Nutrisi Magnesium dari MgSO4.7H2O dan Besi Dari FeSO4.7H2O Pada Kultivasi Tetraselmiss chuii Terhadap Kandungan Lipid Maksimum - Anggi Pratiwi (Inovasi Pembangunan : Jurnal Kelitbangan, 2019)
This study discusses the effect of adding magnesium nutrients from MgSO4.7H2O and iron from FeSO4.7H2O to obtain maximum lipid levels in Tetraselmis chuii microalgae. The nutritional variations used were 0, 4, 6, 8 gr / L MgSO4.7H2O and 0, 24, 30, and 36 µM / L FeSO4.7H2O. Microalgae was cultivated with a photobioreactor filled with 1 L microalgae culture with a ratio of microalgae and sea water 3: 7, namely 300 ml of microalgae and 700 ml of sea water with salinity of 30 ppt. The light intensity is 2000 lux. The study began with culturing microalgae with variations in these nutrients. Then, the cell density is observed every 3 hours until the optimum time is obtained where the cell density is high. Then the microalgae is harvested and extracted so that the lipids are obtained. The extraction process was carried out using diethyl ether solvents. After obtaining the lipid mass, the microalgae lipid levels were calculated. The results showed that the highest lipid levels in Tetraselmis chuii microalgae were obtained by the addition of MgSO4.7H2O 6 gram and the addition of FeSO4.7H2O 36 µM which was 20,175%.